Studying the interactive role of authentic leadership and psychological capital in personnel’s personal and organizational identification - nour mohammad yaghoubi; samaneh mohammadpour; amin reza kamalian (پژوهش‌های روانشناختی در مدیریت)
Organizational Identification is one of the most challenging organizational issues. That's why a lot of attention has been paid to it in the literature on organizational behavior and management research. The purpose of the present study is to study the impact of the most recent leadership approach called authentic leadership on the Personal and Organizational Identification, Given the Mediatory Role of Psychological Capital. Research methodology is descriptive-correlational, and in terms of purpose, it is an applied study. Statistical population includes the employees of National Oil Products Distribution Company of Sistan and Baluchestan Province, out of which 165 individuals were selected through random sampling. Data collection tool includes the standard questionnaires of Avolio et al authentic leadership (2007), questionnaire of Luthans Psychological capital (2007), questionnaire of Cheek & Briggs Personal Identification (2013), questionnaire of Mael & Ashforth Organizational Identification (1992), whose content validity was confirmed by experts’ comments and its reliability was confirmed by Cronbach’s alpha. In this research, correlation test, regression test and structural equations model were used, and data were analyzed using LISREL and SPSS Software. Results indicated that authentic leadership directly and indirectly affects Personal and Organizational Identification through psychological capital. Also, the psychological capital, as a mediator variable, is relatively effective in the relationship between authentic leadership and Psychological capital and Organizational Identification.